Edukasi Diabetes Melitus dan Pemeriksaan Glukosa Darah Acak serta Asam Urat Sebagai Upaya Preventif Penyakit Komorbid Covid-19 - Urip Harahap; Ade Sri Rohani; Hari Ronaldo Tanjung; Dadang Irfan Husori; Khairunnisa Khairunnisa; Embun Suci Nasution (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Diabetes mellitus is one of the comorbid Covid-19, leading cause of death after kidney and heart disease. Lack of understanding related to diabetes mellitus and its prevention in the community in Karya Jati sub-district, North Binjai, Binjai City and the lack of medical check-up including random blood glucose and uric acid levels make education about diabetes mellitus necessary. This program aimed to increase participants knowledge in Karya Jati sub-district, North Binjai, Binjai City about diabetes mellitus, signs/symptoms, prevention, risk factor, life style, and diabetes as covid-19 comorbidity. This program was carried out using the Active Participant Learning Method (CBPA) and medical check-up including random blood glucose and uric acid levels, as well as monitoring and evaluation of community service. Based on T-Test, the results of the pre-test and post-test analysis showed an increase in participants' knowledge about diabetes significantly (p<0.05).